The use of recombinant DNA plasmids for the determination of DNA-repair and recombination in cultured mammalian cells. - Cox, R. (Nature Publishing Group, 1984)
Using the recombinant plasmid pSV2gpt and DNA transfer techniques, cell mediated DNA ligation and recombination of plasmid DNA have been demonstrated in four human cell lines. Data suggesting the involvement of a possible defect in the cellular equilibrium between ligation and exonuclease digestion of double strand DNA scissions in an ataxia-telangiectasia (A-T) cell line is discussed. The same A-T line was grossly proficient in DNA recombination but it will be necessary to distinguish between recombination in coding and non-coding plasmid sequences.